PENGARUH MODEL RADEC TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK KELAS III SEKOLAH DASAR NEGERI BIBISLUHUR 1 SURAKARTA - Lisa Juniar Irawati; Hera Heru Sri Suryanti; Jumanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on the scientific literacy skills of third-grade students at SD Negeri Bibisluhur 1 Surakarta. The background of this research is the low scientific literacy ability of students, particularly in critically, creatively, and contextually understanding scientific concepts, which is influenced by the dominance of conventional learning models that do not actively engage students. This study used a quantitative method with a quasi-experimental design of the one group pretest-posttest type. The population was all third-grade students of SD Negeri Bibisluhur 1 Surakarta in the academic year 2024/2025, and a total of 28 students from class III A were selected through purposive sampling. Data were collected using written tests, observation, and documentation. The test instruments were validated using validity and reliability tests and analyzed with normality and hypothesis testing through a paired sample t-test using SPSS version 25. The results showed a significant improvement in students’ scientific literacy after the implementation of the RADEC model. The average pretest score was 51.07, which increased to 78.93 in the posttest. The paired sample t-test produced a significance value of 0.000 < 0.05, indicating that the RADEC model had a significant effect on scientific literacy. This improvement was evident in three main indicators: the ability to explain scientific phenomena, the ability to design and evaluate scientific questions, and the ability to interpret scientific data and evidence logically.